Paradigma Baru Sistem Kesejahteraan Pegawai; Solusi Alternatif Dan Prospek Implementasinya Di Indonesia Bagian 2 Seri Sistem Kesejahteraan Aparatur - Riyadi Riyadi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
Weaknesses in the payroll system that the principles of justice in this system, institutionally tend not running Governments are required to firmly establish the same civil service salary structure, both for the central and regional levels . Of course this formula needs to be formulated in such a way that opportunities for gaps that are too high can be avoided Salary structure models offered by Research Team PKP2A I LAN is based on a model of the structure of the model with the merit system Composite Scale . Merit system geared to the principle that the salary system should have values objectivity based on work performance and the performance by considering the competence of the employees so that they feel valued in proportion. Meanwhile, Combined Scale, because in this case the team still considers that the two components are fixed and not fixed, it is still necessary in the model calculations in the PNS The persistence of the benefit system in addition to the determination of salary based on grade or rank/class of employees . In addition the models offered , the team seeks to design it with a combination of salary determination in the bureaucratic system of government with the establishment of Provincial Minimum Wage ( LIMP ), which is converted to the National Minimum Wage ( UMN ) as a result of the average minimum wage . Efforts to adopt UMP value in the payroll system is intended to Value Private payroll in environments with in the government there is a ''sameness'', although the similarities are not as a whole. Mix reason is also because Team considers that the system of wage/salary for civil servants with private systems should be in the same setting . It means that the policy is not a separate and partial, but must constitute a form of comprehensive systems and complement each other in the same policy